The use of local anaesthesia in general practice. Issue 7 (July 2015) - Williams, Catrin
The term anaesthesia is from the Greek and means 'loss of sensation'. It enables painful and invasive procedures to be performed with little distress to the patient. Local anaesthesia is a method used to apply anaesthetic to one site, usually topically or subcutaneously. The first recorded use of a local anaesthetic to provide anaesthesia for a surgical procedure was in 1884 when Koller used cocaine to anaesthetise the eye. This initially led to widespread enthusiasm and use of cocaine; however, this was soon tempered by reports of toxic effects and death. Minor surgery in primary care has been shown to be cost-effective and popular with patients. Despite an improvement in the safety of local anaesthetics it is important to get the correct dose and type of anaesthetic and to be aware of potential adverse effects.